163k views
2 votes
Translate this verbal expression into an algebraic equation and solve: thirteen less than twice the sum of a number and six is 47.

you must also give the equation.

User Karthick C
by
4.9k points

1 Answer

8 votes

Answer:

Please check the explanation.

Explanation:

Given the verbal expression

''Thirteen less than twice the sum of a number and six is 47''.

Let us break down the verbal expression into an algebraic equation

  • Let the number be = n
  • Twice the number n = 2n
  • Sum of twice the number and six = 2n+6
  • Thirteen less than twice the sum of a number and six = 2n+6-13

And finally

Thirteen less than twice the sum of a number and six is 47:

2n+6-13 = 47

Therefore, the equation is:
2n+6-13 = 47

Solving the algebraic expression

solving the equation for 'n'


2n+6-13 = 47


2n-7=47

Add 7 to both sides


2n-7+7=47+7

Simplify


2n=54

Divide both sides by 2


(2n)/(2)=(54)/(2)

Simplify


n=27

User Gunjan Shah
by
5.5k points